Maximizing environmental validity: remote recording of desktop videoconferencing - Rintel, Sean (HCII 2007, 2007)
This paper discusses the development of the technical methodology for remote recording to maximize environmental validity for a project on how novices develop familiarity with desktop videoconferencing (DVC). It is also a discussion of how the technical setup, as well as the resulting data, was usefulfor finding usability issues for the company that provided the DVC software.